Decentralizing Education in Transition Societies : Case Studies from Central and Eastern Europe - Fiszbein, Ariel (Washington, DC: World Bank, 2013)
Starting in the fall of 1997, the World Bank Institute organized a learning program on Intergovernmental Roles in the Delivery of Education Services in the Czech Republic, Hungary, Poland and Romania. Bulgaria and Albania joined in 1998. The program aimed to help build analytical capacity to understand the ways that existing and future intergovernmental arrangements infringe on the effectiveness of service delivery in the education sector. Country teams prepared country assessments of intergovernmental arrangements in the education sector. Each country report reviewed the roles being played by different actors in the system, analyzed the main contradictions emerging from those roles, and developed a set of proposals directed to resolving those contradictions. These reports provided basis for a program of group learning under which the teams from different countries exchanged views and learned from each other through a series of workshops and seminars. The overview in this book introduces the concept of institutions and the methodology of institutional analysis used in the program, It also discusses the group learning approach used. It also presents a preliminary assessment of substantive lessons regarding the implications of service delivery. The following country chapters provide a systematic and updated view of where the different countries involved are in terms of reforming the governance structure in their education systems.